DANGERS AND SAFETY MEASURES IN A MOUNTAIN - Jovica Petković; Aldijana Muratović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Mountaineering and everything that is connected with it is a sport with con¬tro¬lled risk. Mountaineers, alpinists, climbers, cavers and all the others who visit and sojourn in mountains are faced with many risks and dangers, which are caused by na¬ture and also by their own mistakes. The dangers in the mountains, like dangers in any other environment, are mainly predictable, so it is best to deal with them with good esti¬mation, knowledge and skill. One has to be aware of his surroundings - the moun¬tain, to respect it and to know what is dangerous and how much it is dangerous at any moment. The organization of the mountaineering expeditions and leadership per¬haps re¬present the highest level of security control. To develop skills for organizing and lead¬ing a group means to ensure the safety of the entire group - to work pre¬ven¬ti¬ve¬ly at the level of the entire group, not only at the level of an individual. The success of the enti¬re group as well as safety depends on the organization and leadership.